КИНОПУБЛИЦИСТИКА ЖӘРДЕМИНДЕ ХАЛЫҚТЫҢ ЭКОЛОГИЯЛЫҚ САНА-СЕЗИМИ ҲӘМ МӘДЕНИЯТЫН РАЎАЖЛАНДЫРЫЎ - Тажадинова, Г.Н. (FAN va JAMIYAT, 2022)
This article discusses the current state of film documentary in Karakalpakstan and its contribution to the development of environmental awareness and culture of the population of the Republic. The peculiarities of the formation of culture through journalistic means are revealed by the method of upbringing with the help of silent film, which belongs to the film documentary.